The influence of personal selling on purchasing decisions study on G99 leather shop leather crafts products - Yusuf Tojiri Yusuf (Jurnal Mantik, 2024)
This research is motivated by the phenomenon of consumer behavior in purchasing leather craft products, where leather craft products are included as exclusive products that need to get the company's attention, so that the company is right in implementing its marketing strategy. The purpose of this research is to determine the influence of personal selling on purchasing decisions at G99 Leather Shop. The research method used in this research is descriptive and associative methods. The analysis techniques used are validity test, reliability test, simple correlation test, determination test and t test. Based on the results of data processing obtained using SPSS Version 22 for Windows software, the instrument used in this research was declared valid and reliable because it had a value greater than the r table of 0.344. Based on the results of the t test (partial), it shows that the significance value of the influence of incentives (X) on purchasing decisions (Y) is 0.000 < 0.005, so the hypothesis is accepted and the calculated t value is 23,762 > t table value 1,668, so H0 is rejected and Ha is accepted. Thus, it is obtained that the hypothesis states that there is a significant influence between personal selling on purchasing decisions at the G99 Leather Shop. From the results of these statistical tests, the author suggests always maintaining personal selling because it influences purchasing decisions for G99 Leather Shop products, so that existing income increases and gets maximum results